Modular acetabular reconstructive cup in acetabular revision total hip arthroplasty at a minimum ten year follow-up - Sakai, Takashi (Springer-Verlag, 2013)
PURPOSE: Modular acetabular reconstructive cups have been introduced in an attempt to offer initial rigid fixation by iliac lag screws and ischial pegs, to support bone grafts with a flanged metal socket, and to restore original hip center in acetabular revision. The purpose of this study was to clarify minimum ten year follow-up results of this cup system with morsellised allografts in revision cases. METHODS: We retrospectively investigated 54 acetabular revisions at a mean of 11 years (range, ten to 14 years). The indications were Paprosky’s type 2B (eight hip), 2C (eight hips), 3A (23 hips), 3B (nine hips), and 4 (six hips). RESULTS: Using aseptic loosening as the endpoints, the survival rate was 89.3 % (95 % CI 81–98). Radiographically, one type 3A hip, three type 3B hips and one type 4 hip showed aseptic loosening while no type 2 hips or no cemented cups showed loosening. CONCLUSIONS: The modular reconstructive cups for acetabular revision showed bone stock restoration and stable implantation.